Pengaruh Pemberian Air Kelapa Muda Dengan Penurunan Tekanan Darah Pada Pasien Hipertensi - . Ayatullah (PEDAGOGOS : Jurnal Pendidikan, 2021)
Hypertension is a health problem that has been becoming the first killing disease in the world. Almost one billion people in the world suffer from hypertension and a quarter of these people were mostly adult. Hypertension is also places the first rank of diseases that lead to mortality in community health centers and Puskesmas in Tolowata According to the data of Tolowata 1 Community Health Ambalawi, especially in Tolowata Village Kecamatan Ambalawi Kabupaten Bima, there were 24% people in the village suffered from hypertension. One of non-pharmacological treatment for hypertension is by consuming young coconut water. The objective of the research is to investigate the effect of young coconut water therapy toward blood pressure on hypertension patient in Village Tolowata Kecamatan Ambalawi Kabupaten Bima. The research employed quasi One Group Pre Test-Post Tes Desig. The plan of this research was in a form of equivalent controled group design. The sampling technique used in the research was nonprobability sampling by using purposive sampling. There were 10 respondents involved in the research. The respondents were divided into two groups, 2 respondents belonged to experimental group and other 5 respondents belonged to controlled group. The result of mann-whitney test on systole and dyastole blood pressure before and after being given the treatment on first and second group was as follow, p-value equaled to 0,012<0,05 and 0,001<0,005. There is an effect of young coconut water therapy toward blood pressure on hypertension patients in Village Tolowata Kecamatan Ambalawi Kabupaten Bima.